Relationship between secondary metabolites and ecological suitability zones for Eucommia ulmoides - Ting Yao; Ya Wang; Na Zhang; Beichao Wang; Zhuoting Gan (PLoS ONE, 2025)
The quality of Chinese medicinal materials is closely related to the types and contents of their secondary metabolites, while ecological adaptability influences the production of secondary metabolites. Therefore, identifying the relationship between ecological adaptability and secondary metabolites is important for enhancing the quality of Chinese medicinal materials. In this study, we collected 10-year-old Cortex Eucommiae (Eucommia ulmoides, EU) samples from 21 plots in eight provinces which are the primary production areas of EU in central China. We used the MaxEnt model to determine the ecological suitability zones for EU at the 21 sampling sites and classified them accordingly. The contents of six pharmacologically active secondary metabolites, including chlorogenic acid, aucubin, geniposidic acid, geniposide, pinoresinol monoglucoside, and pinoresinol diglucoside were measured in the EU bark. The results demonstrated significant variations in the content of the six secondary metabolites in EU bark among different sampling sites. Correlation analysis indicated a close relationship between the content of chlorogenic acid and aucubin in EU bark and the ecological suitability of their respective production areas. The total content of the six secondary metabolites also showed good consistency with the ecological suitability of the production areas. Exploratory factor analysis further revealed a strong consistency between the factor analysis comprehensive scores based on the content of major secondary metabolites and the types of suitability zones at the sample locations. The cluster analysis results demonstrated good consistency between clustering groups and ecological suitability zone groups, with higher consistency as the suitability level of the ecological zone increased. This indicated a significant impact of suitable ecological environments on the content of EU secondary metabolites.